Making Desistance Recognizable: how Ex-Offenders Can Signal Their Desistance From Crime to Employers by Strategic Design - Reich, Suzanne (The British journal of criminology, 2023)
One of the primary concerns employers hold about hiring an ex-offender is the potential reoffending risk they pose. However, criminological literature shows that an ex-offender may be able to mitigate employers’ concerns by signalling their desistance from crime. Less understood is how ex-offenders can signal their desistance to (a) make desistance recognizable and (2) communicate desistance signals that employers value. This article draws on the results from the second phase of an Explanatory Sequential Mixed Methods study with a sample of Australian employers who participated in semi-structured interviews (n = 43). The findings show desistance signals can be communicated to employers via strategic design. These findings along with the theoretical and policy implications are then discussed.